Cover Image. Issue 3 (9th March 2018) - May, Jan‐Hendrik; Huang, He‐Qing; Fujioka, Toshiyuki; Fink, David; Codilean, Alexandru; Yu, Guo‐An; Ma, Yuanxu; Wulf, Gerwin; Gu, Jing
Abstract : The cover image, by Jan‐Hendrik May et al., is based on the Research Article Evolution of sandstone peak‐forest landscapes – insights from quantifying erosional processes with cosmogenic nuclides, DOI:10.1002/esp.4273 . Photo Credit: Jan‐Hendrik May. Image Credit: Zhangjiajie UNESCO Global Geopark of China.